2012
DOI: 10.5005/jcdp-13-4-554
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cervical Preflaring of Root Canal on Determination of Initial Apical File using Gates Glidden Drills, Protaper, Race and Diamond-Coated Galaxy Files

Abstract: Aim To investigate the influence of cervical preflaring on apical file size determination using four different rotary instruments. Materials and methods Fifty root canals from extracted human maxillary premolars with complete root formation, straight roots were used for the study. Access opening was done and the working length established with 8 no K-file for each canal. Teeth were randomly divided into five groups of 10 canals. In Group 1- no preflaring was done and acted as control and in Groups 2, 3, 4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Several studies have reached a similar conclusion. [2,6,[10][11][12][13] The effect of preflaring with Gates Glidden burs and flare files were ranked in intermediary position with statistically similar results in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have reached a similar conclusion. [2,6,[10][11][12][13] The effect of preflaring with Gates Glidden burs and flare files were ranked in intermediary position with statistically similar results in this study.…”
Section: Discussionsupporting
confidence: 72%
“…This approach to determining the initial file size was consistent with research undertaken by Pecora et al [ 15 ], Schmitz et al [ 24 ], Tennert et al [ 10 ], and Sharma et al [ 18 ]. In the majority of the investigations [ 10 , 26 ], the teeth were cut horizontally 1 mm away from the tip, which could potentially impact the binding of the instrument at the WL. In this investigation, the teeth were cut horizontally 0.5 mm away from the tip with a diamond sectioning disk (0.2 mm thick, 1-inch diameter) to reveal the canal and the instrument at the WL.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant differences were found among various rotary instruments in another study 123 . Another investigation showed that coronal preflaring with RaCe instruments led to an accurate determination of the initial apical file followed by ProTaper, Galaxy files (Plastic endo, Lincolnshire, IL), and GG drills 124 . Overall, researchers showed that coronal preflaring related to the crown-down technique increases the accuracy of the determination of constriction diameter.…”
Section: Preflaringmentioning
confidence: 99%